Flexible polymer antifouling tablecloth and preparation method thereof

Through the synergistic effect of the use of modified polyurethane resin and other components in the tablecloth, the problems of poor functional superposition, insufficient durability and environmental protection in the prior art are solved, and the comprehensive performance of flexibility, anti-fouling, self-repair and weather resistance are achieved.

CN119931321AActive Publication Date: 2025-05-06XINGYUAN HLDG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510428978.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-05-06
Estimated Expiration
2045-04-08

AI Technical Summary

Technical Problem

The existing functional tablecloths have shortcomings in functional superposition, durability and environmental protection, and it is difficult to integrate multiple functions such as antibacterial, hydrophobic, and self-healing on the same substrate, and are prone to fall off during use. Some processes rely on environmentally burden-based additives.

Method used

Components such as modified polyurethane resin, carboxylated carbon nanotubes, surface modified nanosilica, citrate plasticizer, nanosilver particles, microencapsulated polyurethane self-repairing agent and benzotriazole ultraviolet absorbers are used to achieve comprehensive performance of flexibility, anti-fouling, self-repairing and weather resistance through synergistic action.

Benefits of technology

The integration of multiple functions is achieved, the durability and antibacterial properties of the material are improved, environmental pollution is avoided, and the self-repair rate reaches ≥85%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119931321A_ABST
    Figure CN119931321A_ABST
Patent Text Reader

Abstract

The invention relates to the related technical field of high polymer materials, and discloses a flexible polymer antifouling tablecloth and a preparation method thereof. Comprising the following components in parts by weight: 40 to 55 parts of modified polyurethane resin, 0.5 to 2 parts of carboxylated carbon nanotubes, 5 to 10 parts of surface modified nano silicon dioxide, 8 to 12 parts of a citrate plasticizer, 2 to 5 parts of nano silver particles, 3 to 6 parts of a microencapsulated polyurethane self-repairing agent, 0.5 to 1.5 parts of a benzotriazole ultraviolet light absorber and 0.1 to 0.3 part of azodiisobutyronitrile. The antibacterial rate is increased and the high tensile strength is maintained through the synergistic matching of the carboxylated carbon nanotubes and the nano-silver, and the combination of the polyurea microcapsules and the surface modified nano-silica enables the material to maintain the high self-repairing rate and not to affect the surface hydrophobicity at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field related to polymer materials, and more specifically, particularly relates to a flexible polymer antifouling tablecloth and a preparation method thereof. Background Art

[0002] With the upgrading of consumption and the enhancement of safety awareness, the functional requirements of textiles in modern homes and public places have shifted from single protection to multi-dimensional performance integration such as antibacterial, antifouling, and durability. Tablecloths, decorative fabrics and other products must not only meet basic requirements such as daily splash protection and wear resistance, but also have intelligent properties such as long-term antibacterial and self-repair to cope with complex usage scenarios. The current mainstream functional tablecloths mainly rely on surface finishing technology to achieve performance improvement by coating or impregnating functional additives on the substrate, but this technical route has the following common defects: Poor functional superposition: Existing processes mostly use step-by-step processing or single functional additives, making it difficult to integrate multiple functions such as antibacterial, hydrophobic, and self-healing on the same substrate. For example, coating-type hydrophobic agents will hinder the penetration of antibacterial ingredients, and solvent compatibility issues in the impregnation process will cause the functional components to fail, and the final product performance can only achieve a single advantage; Insufficient durability: Functional additives are mostly attached to the surface of the substrate by physical adsorption or simple cross-linking, and are easily removed by external forces such as friction and cleaning during long-term use; In order to achieve rapid film formation or lasting functionality, some processes rely on environmentally burdensome additives such as fluorinated compounds and plasticizers, which are easily migrated and released in high temperature or humid environments, posing safety risks.

[0003] Therefore, in view of this, the existing structure and defects are studied and improved, and a flexible polymer anti-fouling tablecloth and a preparation method thereof are provided, in order to achieve a more practical purpose. Summary of the invention

[0004] The invention provides a flexible polymer antifouling tablecloth and a preparation method thereof, which are used to overcome the above-mentioned defects in the prior art.

[0005] The purpose and efficacy of the flexible polymer antifouling tablecloth and the preparation method thereof of the present invention are achieved by the following specific technical means: A flexible polymer antifouling tablecloth comprises the following components: 40-55 parts of modified polyurethane resin, 0.5-2 parts of carboxylated carbon nanotubes, 5-10 parts of surface-modified nano-silicon dioxide, 8-12 parts of citrate plasticizers, 2-5 parts of nano-silver particles, 3-6 parts of microencapsulated polyurethane self-healing agents, 0.5-1.5 parts of benzotriazole ultraviolet absorbers, and 0.1-0.3 parts of azobisisobutyronitrile.

[0006] It should be noted that this scheme defines the basic formula framework of anti-fouling tablecloths. The various components work synergistically to achieve the comprehensive properties of flexibility, anti-fouling, self-repairing and weather resistance. Among them, the modified polyurethane resin is used as the matrix material, and its flexibility and wear resistance are better than PVC or ordinary polyethylene. The soft segment (polyether / polyester) in the polyurethane molecular chain provides elasticity, and the hard segment (urethane) gives strength. The tablecloth can be folded repeatedly without cracking and is resistant to oil penetration; the addition of carboxylated carbon nanotubes solves the problem that traditional fillers (such as carbon black) are difficult to be added at low dosages. In order to take into account both the conductivity and mechanical reinforcement, the carboxyl group forms hydrogen bonds with the polar groups of the polyurethane to enhance the interfacial bonding strength, the carbon nanotube network structure imparts antistatic properties, the surface of the tablecloth is not easy to absorb dust, and the tensile strength is improved; unmodified nano-silica is easy to agglomerate, resulting in material embrittlement, while the modified nano-silica in this scheme, the silica surface modified by the silane coupling agent (such as KH-570) contains organic segments, which is more compatible with polyurethane, and the surface hardness of the tablecloth is moderate, which is both scratch-resistant and soft to the touch.

[0007] Citrate plasticizers are used to replace traditional phthalate plasticizers (such as DEHP) to avoid possible environmental hormone risks. Phthalates have been restricted due to their potential toxicity. Citrate is an environmentally friendly alternative with higher safety. At the same addition amount, the plasticizing efficiency of triethyl citrate is equivalent to that of DEHP, and there is no migration risk. Nanosilver particles solve the problem of organic antibacterial agents (such as quaternary ammonium salts) being volatile and having poor durability. The sustained release of silver ions destroys the cell membrane of microorganisms, and the antibacterial rate against Escherichia coli and Staphylococcus aureus lasts for more than 6 months. Scratches on the surface of traditional tablecloths cannot be repaired by themselves, affecting their appearance and service life. Microencapsulated polyurethane self-healing agent is added to the formula, in which the microcapsule shell (polyurea) protects the core material (polyurethane prepolymer). After damage, the prepolymer cross-links and solidifies when exposed to moisture, which is conducive to self-repair.

[0008] According to a further technical solution, the carboxyl content of the carboxylated carbon nanotubes is 2-5 wt %.

[0009] It should be noted that a carboxyl content of 2-5 wt% can balance dispersibility and reactivity. A carboxyl content that is too low (<2%) cannot effectively react with polyurethane, while a carboxyl content that is too high (>5%) causes the carbon nanotubes to be too hydrophilic and their compatibility with the hydrophobic matrix decreases.

[0010] According to a further technical solution, the citrate plasticizer is triethyl citrate or tributyl citrate; the shell material of the microencapsulated polyurethane self-healing agent is polyurea or polyurethane, and the core material is a polyurethane prepolymer.

[0011] It should be noted that triethyl citrate is more environmentally friendly than phthalates and has better compatibility with polyurethane.

[0012] In a further technical solution, the particle size of the nanosilver particles is 10-50 nm, and the particle size of the microencapsulated polyurethane self-healing agent is 5-20 μm.

[0013] It should be noted that nanosilver particles with a diameter of less than 10 nm are easily oxidized and inactivated, and the antibacterial efficiency drops sharply when the particle size is greater than 50 nm. Microencapsulated polyurethane particles with a diameter that is too small (<5 μm) are prone to rupture during processing, and microcapsule particles that are too large (>20 μm) affect the surface smoothness of the tablecloth.

[0014] According to a further technical solution, the modifier of the surface-modified nano-silica is a silane coupling agent, and the surface hydroxyl content thereof is 3-8 wt%.

[0015] It should be noted that silica modified with silane coupling agent (hydroxyl content 3-8 wt%) can balance dispersibility and reactivity. If the hydroxyl content is too low (less than 3%), the modification effect is poor, while if the hydroxyl content is too high (more than 8%), it is easy to absorb water and cause interface defects.

[0016] In a further technical solution, the benzotriazole ultraviolet absorber is UV-327 or UV-328.

[0017] It should be noted that UV-327 (long-chain alkyl substitution) has better migration resistance than UV-328 and is suitable for outdoor scenes; UV-328 has lower cost and is suitable for indoor scenes. A method for preparing a flexible polymer antifouling tablecloth comprises the following steps: Step a, mixing modified polyurethane resin, carboxylated carbon nanotubes, surface-modified nano-silicon dioxide, citrate plasticizer, nano-silver particles, microencapsulated polyurethane self-healing agent, benzotriazole ultraviolet absorber and azobisisobutyronitrile in proportion and stirring evenly; It should be noted that during the implementation process, the resin and plasticizer should be mixed first, and then the nanomaterials should be gradually added to avoid direct contact between nanosilver and carbon nanotubes, which would lead to the premature formation of a conductive network.

[0018] Step b, forming the mixed material into a tablecloth substrate through a molding process; Step c, performing surface treatment on the formed tablecloth.

[0019] According to a further technical solution, the stirring speed of the mixing in step a is 500-1000 rpm, and the stirring time is 10-20 min.

[0020] According to a further technical solution, the forming process in step b is calendering, and the roller temperature of the calendering is 80-120°C.

[0021] In a further technical solution, the surface treatment in step c comprises an embossing or coating process, wherein a fluorine-containing polymer coating is used in the coating process.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) Synergistic antibacterial network of carboxylated carbon nanotubes and nanosilver: The abundant carboxyl functional groups on the surface of carboxylated carbon nanotubes combine with nanosilver particles through coordination to form a continuous silver ion transmission channel, which significantly improves the silver ion release rate and targeted adsorption capacity, avoiding the agglomeration failure problem caused by the single addition of nanosilver. At the same time, the carbon tube network delays the oxidation of silver particles, thereby improving the antibacterial durability.

[0023] (2) Repair synergistic mechanism of polyurea microcapsules and nanofillers: The gradient shell thickness design of polyurea microcapsules is combined with the surface catalytic effect of nano-SiO2 to achieve a balance between the structural integrity of the microcapsules during the processing process and the self-repair efficiency during the use stage; the repair agent released after the microcapsule ruptures migrates to the crack area through the carbon nanotube network, and the hydroxyl groups on the SiO2 surface accelerate the repair cross-linking reaction, so that the 24h repair rate reaches ≥85%; (3) Multi-level combination of environmentally friendly hydrophobic system: PTFE fluorine-free coating and citrate plasticizer are anchored to the polyurethane matrix through hydrogen bonding to form a stable hydrophobic interface; the micro-nano rough structure on the surface of the microcapsule and the coating synergistically reduce the solid-liquid contact area, and the water contact angle is ≥112°; (4) Dynamic balance between self-repair and antibacterial functions: Silver nanoparticles are embedded in the shell of polyurea microcapsules, replenishing the surface silver ion concentration while the repair agent is released, preventing the local antibacterial performance from decreasing due to microcracks; carbon nanotubes serve as antibacterial agent carriers and mechanical reinforcement phases to achieve functional consistency before and after material damage. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a comparison diagram of tensile strength and water contact angle of Examples 1 to 6 of the present invention; Figure 2 This is a correlation analysis diagram of antibacterial properties and self-repairing properties of Examples 1 to 6 of the present invention; Figure 3 It is a performance comparison diagram of Example 1, Comparative Example 1 and Comparative Example 4 in the present invention; Figure 4 It is a trend diagram of silver ion release rate of Example 5 and Comparative Example 5 in the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] Performance Indicators Test Parameters Test Standards / Methods Mechanical properties Tensile strength, elongation at break GB / T 1040.3-2006 Antifouling performance Water contact angle, oil adhesion rate GB / T 30693-2014 Antimicrobial Antibacterial rate against Escherichia coli / Staphylococcus aureus ISO 22196-2011 Self-healing Microcrack healing rate (24h) Microscope observation + image analysis Weather resistance Color difference after UV aging (ΔE) GB / T 14522-2008 .

[0027] Note that all performance tests are carried out under a standard environment with a temperature of 23±2℃ and a relative humidity of 50±5%, and the sample pretreatment time is ≥24h.

[0028] Embodiment 1: This embodiment provides a flexible polymer antifouling tablecloth, and the preparation method thereof comprises the following steps: Step a: premix 50 parts of modified polyurethane resin and 10 parts of triethyl citrate plasticizer in a stirring kettle at a speed of 800 rpm for 5 minutes to fully plasticize the resin.

[0029] It should be noted that the modified polyurethane resin is a hydroxyl-terminated type with a hydroxyl value of 45-60 mg KOH / g, and is prepared by reacting polytetramethylene glycol (Mn=2000) with isophorone diisocyanate at a ratio of NCO:OH=1.05:1.

[0030] 1 part of carboxylated carbon nanotubes (carboxyl content 3 wt%), 8 parts of surface-modified nano-silica (KH-570 modified, hydroxyl content 5 wt%), and 3 parts of nano-silver particles (particle size 30 nm) were added in sequence, and stirring was continued for 10 min to ensure that the nanomaterials were evenly dispersed.

[0031] It should be noted that the KH-570 modification method of nano-silica is as follows: 10 g of nano-SiO2 is dispersed in an ethanol / water (4:1) solution, 3 wt% of KH-570 coupling agent is added, refluxed at 80 °C for 6 h, and centrifuged and dried to obtain.

[0032] Finally, 4 parts of microencapsulated polyurethane self-healing agent (particle size 10 μm, shell layer is polyurea, core material is polyurethane prepolymer), 1 part of UV-327 ultraviolet absorber, and 0.2 parts of azobisisobutyronitrile were added and stirred at low speed (500 rpm) for 5 min to avoid destroying the microcapsule structure.

[0033] It should be noted that the microcapsule preparation process is as follows: polyurethane prepolymer (Desmophen 670A) and TDI (toluene diisocyanate) are mixed in a ratio of 1:1.2 as the core material, 1% polyvinyl alcohol is used as an emulsifier, emulsified at 2000 rpm to form a W / O emulsion, hexamethylenediamine is added for interfacial polymerization, and the polyurea shell layer is obtained by reacting at 60°C for 4 h.

[0034] Step b: The mixed material is formed into a tablecloth substrate with a thickness of 0.5 mm through a calendering molding process, with a calendering roller temperature of 100° C. and a roller speed of 3 m / min.

[0035] Step c: The formed tablecloth was treated with a fluoropolymer coating (PTFE (polytetrafluoroethylene) emulsion) with a coating thickness of 15 μm and cured at 80°C for 10 min.

[0036] Test items Test Results Tensile Strength 28.5 MPa Water contact angle 112° Escherichia coli inhibition rate (24h) 99.8% Microcrack healing rate (24h) 85% UV aging color difference (500h) ΔE=1.2 .

[0037] Example 2: The steps for preparing the flexible polymer antifouling tablecloth in this example are as follows: Step a: Premix 40 parts of modified polyurethane resin and 8 parts of tributyl citrate plasticizer in a stirred tank at a speed of 500 rpm for 5 minutes.

[0038] 0.5 parts of carboxylated carbon nanotubes (carboxyl content 2 wt%), 5 parts of surface-modified nano-silicon dioxide (KH-570 modified, hydroxyl content 3 wt%), and 2 parts of nano-silver particles (particle size 10 nm) were added in sequence, and stirring was continued for 10 min.

[0039] Finally, 3 parts of microencapsulated polyurethane self-healing agent (particle size 5 μm, shell layer is polyurethane, core material is polyurethane prepolymer), 0.5 parts of UV-328 ultraviolet absorber, and 0.1 parts of azobisisobutyronitrile were added and stirred at low speed (400 rpm) for 5 min.

[0040] Step b: calendering (roller temperature 80°C, roller speed 2 m / min) to produce a tablecloth substrate with a thickness of 0.6 mm.

[0041] Step c: Surface embossing treatment (no coating).

[0042] Test items Test Results Tensile Strength 24.8 MPa Water contact angle 108° Escherichia coli inhibition rate (24h) 99.5% Microcrack healing rate (24h) 80% UV aging color difference (500h) ΔE=1.8 .

[0043] Example 3: The steps for preparing the flexible polymer antifouling tablecloth in this example are as follows: Step a: premix 55 parts of modified polyurethane resin and 12 parts of triethyl citrate plasticizer in a stirred tank at a speed of 1000 rpm for 5 min.

[0044] 2 parts of carboxylated carbon nanotubes (carboxyl content 5 wt%), 10 parts of surface-modified nano-silicon dioxide (KH-570 modified, hydroxyl content 8 wt%), and 5 parts of nano-silver particles (particle size 50 nm) were added in sequence, and stirring was continued for 15 min.

[0045] Finally, 6 parts of microencapsulated polyurethane self-healing agent (particle size 20 μm, shell layer is polyurea, core material is polyurethane prepolymer), 1.5 parts of UV-327 ultraviolet absorber, and 0.3 parts of azobisisobutyronitrile were added and stirred at low speed (600 rpm) for 5 min.

[0046] Step b: calendering (roller temperature 120°C, roller speed 4 m / min) to produce a tablecloth substrate with a thickness of 0.4 mm.

[0047] Step c: Fluoropolymer coating (PTFE emulsion, thickness 20 μm), cured at 100 °C for 15 min.

[0048] Test items Test Results Tensile Strength 26.2 MPa Water contact angle 115° Escherichia coli inhibition rate (24h) 99.9% Microcrack healing rate (24h) 88% UV aging color difference (500h) ΔE=1.0 .

[0049] Example 4: The steps for preparing the flexible polymer antifouling tablecloth in this example are as follows: Step a: Premix 45 parts of modified polyurethane resin and 9 parts of tributyl citrate plasticizer in a stirred tank at a speed of 700 rpm for 5 minutes.

[0050] 1.5 parts of carboxylated carbon nanotubes (carboxyl content 4 wt%), 7 parts of surface-modified nano-silicon dioxide (KH-570 modified, hydroxyl content 6 wt%), and 4 parts of nano-silver particles (particle size 40 nm) were added in sequence, and stirring was continued for 12 min.

[0051] Finally, 5 parts of microencapsulated polyurethane self-healing agent (particle size 15 μm, shell layer of polyurea), 1.2 parts of UV-328 ultraviolet absorber, and 0.25 parts of azobisisobutyronitrile were added and stirred at low speed (550 rpm) for 5 min.

[0052] Step b: calendering (roller temperature 110°C, roller speed 3.5 m / min) to produce a tablecloth substrate with a thickness of 0.5 mm.

[0053] Step c: Fluoropolymer coating (PTFE emulsion, thickness 18 μm), cured at 90 °C for 12 min.

[0054] Test items Test Results Tensile Strength 29.1 MPa Water contact angle 114° Escherichia coli inhibition rate (24h) 99.7% Microcrack healing rate (24h) 86% UV aging color difference (500h) ΔE=1.1 .

[0055] Embodiment 5: The formula and process of this embodiment are basically the same as those of Example 1, except that the amount of carboxylated carbon nanotubes is adjusted to 1.2 parts (originally 1 part), the amount of nanosilver particles is adjusted to 4.5 parts (originally 3 parts), and the stirring speed is reduced to 700 rpm to optimize dispersibility.

[0056] Example 6: This example is improved on the basis of Example 4 as follows: the thickness of the shell polyurea of ​​the microencapsulated self-healing agent is increased by 20% (achieved by extending the emulsification time), and the calendering temperature is adjusted to 105°C (originally 110°C). The remaining components and process are the same as in Example 4.

[0057] The calendering temperature adaptability test shows that when the temperature fluctuates by ±10°C, the self-repair rate of Example 6 fluctuates by <3%, while that of Example 1 fluctuates by 8%.

[0058] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Tensile strength (MPa) 28.5 24.8 26.2 29.1 29.3 29.1 Water contact angle (°) 112 108 115 114 112 114 Antibacterial rate (24h) 99.8% 99.5% 99.9% 99.7% 99.8% 99.7% Self-repair rate (24h) 85% 80% 88% 86% 82% 91% UV color difference ΔE (500h) 1.2 1.8 1.0 1.1 1.2 1.1 .

[0059] Experimental data show that the mechanical and surface properties of Examples 1-6 are tested. Figure 1 As shown, mechanical strength (tensile strength) reflects the material's ability to resist fracture when subjected to stress and is a key mechanical indicator of structural materials. Hydrophobicity (water contact angle) characterizes the material surface's repellency to water and directly affects surface properties such as corrosion resistance and anti-fouling. This patent uses a microcapsule-nanosilver synergistic structure to improve mechanical strength while maintaining high hydrophobicity, breaking through the technical bottleneck of traditional materials that are difficult to balance strength and surface performance.

[0060] The tensile strength of Examples 4-6 is >29 MPa, and the water contact angle is stable at 112-115°, which proves that the uniform distribution of nanosilver does not destroy the surface topology and maintains good hydrophobic properties. By controlling the optimal ratio of microcapsule particle size and nanosilver loading, the tensile strength is improved while maintaining a good water contact angle.

[0061] like Figure 2 As shown, the antibacterial and self-repairing properties, the self-repairing rate reflects the material's ability to repair microcracks autonomously, which directly affects the service life; the antibacterial rate reflects the inhibitory effect on microorganisms, which determines the sanitary and safety performance. The microcapsules of the present application release nanosilver when repairing cracks, forming a dual-effect mechanism of "repairing and sterilization".

[0062] When the self-repair rate is greater than 85% (such as in Example 3 and Example 6), the antibacterial rate is greater than or equal to 99.7%, and the trend line shows that the antibacterial rate increases by 0.15% for every 5% increase in the self-repair rate.

[0063] Comparative Example 1 The formula and process of this comparative example are exactly the same as those of Example 1, except that the 4 parts of microencapsulated polyurethane self-healing agent added in step a are deleted, and the amounts of other components and process parameters remain unchanged.

[0064] Test items Comparative Example 1 Example 1 Failure mechanism analysis Tensile strength (MPa) 18.3 28.5 Missing microcapsules lead to inability to disperse stress Microcrack healing rate (24h) 0% 85% No self-repair function Water contact angle (°) 95 112 The hydrophobic structure of the microcapsule surface is missing Escherichia coli inhibition rate (24h) 99.3% 99.8% .

[0065] Comparative Example 2 In this comparative example, 10 parts of triethyl citrate in Example 1 were replaced with an equal amount of DEHP plasticizer, and the stirring speed was increased to 1000 rpm to compensate for the compatibility difference. The other conditions were the same as in Example 1.

[0066] Test items Comparative Example 2 Example 1 Problem Description Tensile strength (MPa) 25.1 28.5 The difference was not significant (p>0.05) Phthalate migration amount (mg / kg) 2.7 (standard limit 1.0) Not detected Exceeds the limit of national standard GB 31604.30-2016 Plasticizer volatility after accelerated aging 12.3%(70℃×7d) 3.1% DEHP has poor thermal stability .

[0067] Comparative Example 3 This comparative example completely adopts the formulation of Example 1, but the calendering temperature in step b is increased from 100° C. to 150° C., and the other parameters remain unchanged.

[0068] The test results are as follows: The self-repair rate dropped from 85% to 45%, the high temperature caused the microcapsules to fail, the diameter of the nanosilver antibacterial zone shrank by 35%, and the particles agglomerated; the conductivity increased by 380%, and the dispersion of nanosilver was destroyed by high temperature.

[0069] The research of Niu Shaoshuai et al. (Journal of Qingdao University of Science and Technology (Natural Science Edition), 2023, 44(3)) shows that when the emulsification speed increases from 1500r / min to 2000r / min, the heat resistance temperature of polyurea microcapsules increases from 238℃ to 277℃, but this data was obtained under the condition of no mechanical stress.

[0070] The present application found that even 150°C can cause functional damage to the microcapsules during the calendering process, proving that the processing conditions have a significant impact on the temperature resistance threshold.

[0071] Comparative Example 4 The preparation steps of this comparative example are as follows: Step a: Premix 50 parts of modified polyurethane resin and 10 parts of triethyl citrate plasticizer in a stirring kettle and stir at 800 rpm for 5 min. Add 1.2 parts of carboxylated carbon nanotubes (carboxyl content 3 wt%, the same as in Example 1), 8 parts of KH-570 modified nano-silicon dioxide, and 0 parts of nano-silver particles in sequence, and continue stirring for 10 min. Finally, add 4 parts of microencapsulated self-healing agent, 1 part of UV-327, and 0.2 parts of azobisisobutyronitrile, and stir at a low speed of 500 rpm for 5 min.

[0072] Steps bc: exactly the same as Example 1 (calendering at 100°C, PTFE coating 15 μm).

[0073] Test items Test Results Comparative Example 1 Difference Analysis Tensile strength (MPa) 26.1 Carbon nanotubes alone have limited reinforcing effects Escherichia coli inhibition rate (24h) 35.2% The absence of nanosilver resulted in a significant decrease in the antibacterial rate Silver ion release rate Not detected Verify silver-free ion release channel Water contact angle (°) 95.0 .

[0074] like Figure 3 As shown, comparative example 1 removes microcapsules to verify its core role in stress dispersion, comparative example 4 cancels nanosilver to confirm its necessity for surface modification, and compared with example 1, comparative example 1 has a 35% decrease in tensile strength when there is no microcapsule, and comparative example 4 has a sudden drop in antibacterial rate to 35% when there is no nanosilver, proving its main bactericidal effect.

[0075] Comparative Example 5 The preparation steps of this comparative example are as follows: Step a: premix 50 parts of modified polyurethane resin with 10 parts of triethyl citrate. Add 0 parts of carbon nanotubes, 8 parts of modified nano-SiO2, and 4.5 parts of nano-silver particles (particle size 30 nm) in sequence, and continue stirring for 10 minutes. The dosage and process of other additives (microcapsules, UV-327, etc.) are the same as in Example 1.

[0076] Step bc: completely the same as in Example 1.

[0077] Test items Test Results Technical Problem Revealed Tensile strength (MPa) 24.7 No carbon nanotube network support Antibacterial rate (24h) 99.1% The silver ion release rate is only 2.8 μg / cm²·h Silver ion release rate 2.8 μg / cm²·h Lack of ion transport channels in carbon nanotubes .

[0078] Comparative Example 6 The preparation steps of this comparative example are as follows: Step a: premix 50 parts of modified polyurethane resin with 10 parts of triethyl citrate. Add 1.2 parts of carboxylated carbon nanotubes (carboxyl content 3 wt%), 8 parts of modified nano-SiO2, and 4.5 parts of nano-silver particles (particle size 30 nm) in sequence, and continue stirring for 10 minutes. The remaining additive amounts and processes are the same as in Example 1.

[0079] Steps bc: exactly the same as in Example 1.

[0080] Test items Test Results Synergy analysis Tensile strength (MPa) 29.5 Carbon nanotubes and silver particles form an interpenetrating network Antibacterial rate (24h) 99.8% 0.7 percentage points higher than comparison example 5 Silver ion release rate 4.2 μg / cm²·h Carbon nanotubes promote the targeted release of silver ions 168-hour antibacterial rate retention rate 98.3% Carbon nanotubes delay oxidation failure of silver particles .

[0081] It should be noted that the silver ion release rate test process in this application is: Extract preparation: Use artificial sweat (sodium chloride 20 g / L, lactic acid 17 g / L, urea 5 g / L, pH=6.5±0.2).

[0082] Test conditions: Sample size: 10×10 cm², immersed in 50 mL artificial sweat.

[0083] Temperature: 37 ± 1 °C, shaking speed: 60 rpm.

[0084] Extraction time: 24 h.

[0085] Quantitative analysis: Inductively coupled plasma mass spectrometry (ICP-MS) was used, with a detection limit of 0.01 μg / L, and the calculation formula was: Release rate = (C×V) / (A×t). (C: silver concentration, V: solution volume, A: sample area, t: time) By comparing and analyzing Comparative Examples 4-6, when only carbon nanotubes (Comparative Example 4) are contained, the antibacterial rate is less than 40%, proving that it has no significant antibacterial effect itself; when only nanosilver (Comparative Example 5) is contained, although the antibacterial rate is >99%, the silver ion release rate is low and the cost is high; the compound of carbon nanotubes and nanosilver (Comparative Example 6) achieves performance breakthroughs through the following synergistic mechanisms: the carbon nanotube network provides a transmission channel for silver ions, the release rate is improved, the carboxyl functional groups adsorb bacteria through electrostatic action, and a high-concentration silver ion "killing zone" is formed locally. Silver particles fill the gaps in the carbon tube network, and the tensile strength is increased by 19.4%.

[0086] like Figure 4 As shown, after 200 h, the release rate of Example 5 was 82% of the initial value, while that of Comparative Example 5 was only 54%. The antibacterial persistence was negatively correlated with the slope of the release rate.

[0087] Comprehensive analysis 1. Analysis of tensile strength The tensile strength of Examples 1-6 showed significant differences (24.8-29.3 MPa). Analysis showed that the differences in mechanical properties were mainly due to the following key factors: (1) When the amount of modified polyurethane resin increased from 40 parts (Example 2) to 55 parts (Example 3), the tensile strength increased by 5.6%, and the hard segment content in the resin molecular chain increased, effectively improving the rigidity of the material.

[0088] (2) Carboxylated carbon nanotubes (0.5-2 parts) are reinforced by two mechanisms, physical reinforcement and chemical bonding. The tubular structure with high aspect ratio (>1000) forms a three-dimensional network in the matrix, and the surface carboxyl groups (2-5wt%) form ester bonds with the hydroxyl groups of the resin. In addition, nano-SiO2 (5-10 parts) also has a reinforcing effect. After KH-570 modification, the surface hydroxyl groups of SiO2 (3-8wt%) form hydrogen bonds with the resin, and the particle size distribution (20-50nm) optimizes the stress transfer efficiency.

[0089] (3) Example 5 (1.2 parts of carboxylated carbon nanotubes + 4.5 parts of nanosilver particles) showed the best strength (29.3 MPa). Its mechanism of action is that the nanosilver fills the gaps in the carbon tube network to form a "brick-and-mortar" structure.

[0090] 2. Analysis of surface hydrophobicity The differences in water contact angles (108-115°) in Examples 1-6 are mainly determined by the following factors: (1) Surface chemical composition: The introduction of the fluorine-containing coating (PTFE) increases the contact angle by ≥6°, with Example 3 (containing fluorine) at 115° being higher than Example 2 (without fluorine) at 108°.

[0091] (2) Interface interaction: The choice of plasticizer (8-12 parts) affects the coating adhesion. Triethyl citrate (Example 3) is more conducive to PTFE spreading than tributyl citrate (Example 2), and the contact angle hysteresis is <5°, which proves that the surface chemical uniformity is good.

[0092] 3. Analysis of antibacterial mechanism The difference in the antibacterial rate (99.5-99.9%) in Examples 1-6 mainly depends on: (1) The release rate of 5-nanometer silver particles (Example 2) is 3 times faster than that of 50-nanometer silver particles (Example 3), but the large particles (50 nm) provide a more lasting antibacterial effect (still 99% inhibition rate after 168 h).

[0093] (2) The "capture-kill" mechanism of carboxylated carbon nanotubes: the surface carboxyl groups adsorb bacteria through electrostatic effects, forming a local microenvironment with high concentrations of silver ions, resulting in a synergistic antibacterial effect.

[0094] 4. Analysis of Self-Healing Performance The self-repair function of the present invention is mainly achieved through the following mechanisms: (1) Microcapsule-triggered repair uses polyurethane prepolymer as the core material. When microcracks occur in the material, stress concentration causes the microcapsules to rupture, and the released prepolymer reacts with moisture in the environment: Main reaction: -NCO + H2O increases to -NH2 + CO2, and the newly generated amino group forms a chemical bond with the resin matrix.

[0095] (2) Factors affecting repair efficiency: When the amount of microcapsules added increased from 3 parts to 6 parts, the repair rate increased from 80% to 88% (Example 2 and Example 3), and the optimal dispersion concentration (6 parts) ensured the connectivity of the repair network.

[0096] (3) With the assistance of nanofillers, the hydroxyl groups (3-8wt%) on the SiO2 surface catalyze the NCO hydrolysis reaction, and the carbon nanotube network provides a channel for the transmission of repair substances.

[0097] The advantages of this application are: 1. Through the synergistic ratio of carboxylated carbon nanotubes (1-2 parts) + nanosilver (3-5 parts), the antibacterial rate > 99.5% and the tensile strength ≥ 28MPa are achieved.

[0098] 2. The combination of polyurea microcapsules (4-6 parts) and modified SiO2 (5-10 parts) makes the self-healing rate exceed 90% without affecting the surface hydrophobicity.

[0099] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A flexible polymer antifouling tablecloth, characterized in that: The invention comprises the following components: 40-55 parts of modified polyurethane resin, 0.5-2 parts of carboxylated carbon nanotubes, 5-10 parts of surface-modified nano-silicon dioxide, 8-12 parts of citrate plasticizer, 2-5 parts of nano-silver particles, 3-6 parts of microencapsulated polyurethane self-healing agent, 0.5-1.5 parts of benzotriazole ultraviolet absorber and 0.1-0.3 parts of azobisisobutyronitrile.

2. The flexible polymer antifouling tablecloth according to claim 1, characterized in that: The carboxyl content of the carboxylated carbon nanotubes is 2-5 wt %.

3. The flexible polymer antifouling tablecloth according to claim 1, characterized in that: The citrate plasticizer is triethyl citrate or tributyl citrate; the shell material of the microencapsulated polyurethane self-healing agent is polyurea or polyurethane, and the core material is polyurethane prepolymer.

4. The flexible polymer antifouling tablecloth according to claim 1, characterized in that: The particle size of the nano silver particles is 10-50 nm, and the particle size of the microencapsulated polyurethane self-healing agent is 5-20 μm.

5. The flexible polymer antifouling tablecloth according to claim 1, characterized in that: The modifier of the surface-modified nano-silica is a silane coupling agent, and the surface hydroxyl content thereof is 3-8 wt%.

6. The flexible polymer antifouling tablecloth according to claim 1, characterized in that: The benzotriazole ultraviolet absorber is UV-327 or UV-328.

7. A method for preparing a flexible polymer antifouling tablecloth, characterized in that: The following steps are involved: Step a, mixing modified polyurethane resin, carboxylated carbon nanotubes, surface-modified nano-silicon dioxide, citrate plasticizer, nano-silver particles, microencapsulated polyurethane self-healing agent, benzotriazole ultraviolet absorber and azobisisobutyronitrile in proportion and stirring evenly; Step b, forming the mixed material into a tablecloth substrate through a molding process; Step c, performing surface treatment on the formed tablecloth.

8. The method for preparing a flexible polymer antifouling tablecloth according to claim 7, characterized in that: The stirring speed of the mixing in step a is 500-1000 rpm, and the stirring time is 10-20 min.

9. The method for preparing a flexible polymer antifouling tablecloth according to claim 7, characterized in that: The forming process in step b is calendering, and the roller temperature of calendering is 80-120°C.

10. The method for preparing a flexible polymer antifouling tablecloth according to claim 7, characterized in that: The surface treatment in step c includes embossing or coating process, wherein the coating process uses a fluorine-containing polymer coating.

Citation Information

Patent Citations

  • Antifouling and antibacterial tablecloth

    CN105860328A

  • Anti-oil stain tablecloth

    CN112322209A

  • Self-repairing long-acting anticorrosive coating material as well as preparation method and application thereof

    CN119505678A

  • Perfluorohexanone microcapsule fire extinguishing material and preparation method thereof

    US20230405381A1

  • KR20220018375A